A Framework for Sensor Fusing Using Fuzzy Logic for Navigation Systems - Kitt, Wong Wei; Chekima, Ali; Dhargam, Jamal A.; Wong, Farrah; A.Tabet, Tamer (Iraqi Journal for Electrical and Electronic Engineering, 2010)
Navigational sensors are evolving both on a commercial and research level. However, the limitation still lies in the accuracy of the respective sensors. For a navigation system to reach a certain accuracy, multi sensors or fusion sensors are used. In this paper, a framework of fuzzy sensor data fusing is proposed to obtain an optimised navigational system. Different types of sensors without a known state of inaccuracy can be fused using the same method proposed. This is demonstrated by fusing compass/accelerometer and GPS signal. GPS is prone to inaccuracies due to environmental factors. These inaccuracies are available in the extracted NMEA protocols as SNR and HDOP. Dead reckoning sensors on the other hand do not depend on external radio signal coverage and can be used in areas with low coverage, but the errors are unbounded and have an accumulative effect over time.